2016
DOI: 10.3382/ps/pew124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary oligosaccharide supplementation on growth performance, concentrations of the major odor-causing compounds in excreta, and the cecal microflora of broilers

Abstract: This study investigated the effects of dietary supplementation with 4 types of oligosaccharides on the growth performance, concentrations of the major odor-causing compounds in excreta and cecal microflora of broilers. Three hundred 21-day-old Archer Abor broilers with an average initial live weight of 702.3 g were randomly divided into 5 dietary treatments: basal diet, basal diet + 5 g/kg of mannan-oligosaccharide (MOS), basal diet + 1.2 g/kg of inulin, basal diet + 1.5 g/kg of fructo-oligosaccharide (FOS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 32 publications
4
61
0
Order By: Relevance
“…Odour emission from chicken excreta is a serious problem in intensive chicken production, and consequently, strategies to mitigate emissions are urgently needed (Yang, Yin, Liu, & Liu, ). It is clear that the odour compounds are produced mainly by the microbial degradation of several substrates in the large intestine of animals (Deng et al., ; Jensen & Hansen, ; Le et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Odour emission from chicken excreta is a serious problem in intensive chicken production, and consequently, strategies to mitigate emissions are urgently needed (Yang, Yin, Liu, & Liu, ). It is clear that the odour compounds are produced mainly by the microbial degradation of several substrates in the large intestine of animals (Deng et al., ; Jensen & Hansen, ; Le et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of poultry feeding with some oligosaccharides, such as inulin and SBO, contributes to the modulation of intestinal microbiota through favouring a quick proliferation of beneficial strains and inhibiting the growth of pathogenic microbes and then reduces the production of odour compounds (Abdelqader, Al‐Fataftah, & Das, ; Buclaw, ; Yang et al., ; Lan, Williams, Verstegen, Patterson, & Tamminga, ). Our former study has shown that broilers that were fed on 1.2 g/kg of inulin or 1.25 g/kg of SBO benefited from uncultured Lachnospiraceae bacteria and Bacteroides sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Quantity One 4.6 (Bio-Rad) was used to analyze the DGGE gel patterns as previously described (Yang et al, 2016)…”
Section: Discussionmentioning
confidence: 99%
“…The Quantity One 4.6 (Bio‐Rad) was used to analyze the DGGE gel patterns as previously described (Yang et al., ). Total number of bands per lane was detected automatically.…”
Section: Methodsmentioning
confidence: 99%